SAT0380 Nsaids Modify The Effect of Tumor Necrosis Factor Inhibitors on New Bone Formation in Ankylosing Spondylitis. (15th July 2016) - Gensler, L.; Reveille, J.D.; Ward, M.M.; Brown, M.A.; Rahbar, M.; Lee, M.; Weisman, M.H.
Abstract : Background: Radiographic damage in Ankylosing Spondylitis (AS) is largely defined by new bone formation. The beneficial effects of pharmacologic therapy on osteoproliferation have been difficult to prove. Objectives: The objective of this study was to examine the relationship of NSAIDs and Tumor Necrosis Factor inhibitors (TNFi) on New bone formation in AS. Methods: 511 AS patients meeting the modified New York criteria with at least 2 years of radiographic follow-up were included in this prospective longitudinal study. Progression was defined as an increase at any vertebral corner from 0/1 to 2 or 0/1 to 3 at any interval between radiographs to reflect syndesmophyte development. We grouped patients according to the interval between baseline and the last visit, and used progression as a dichotomized outcome in a mixed effect logistic regression model. Patients taking NSAIDs for more than 50% of the time between visits were considered high NSAID users for that visit. TNFi use was assessed at each visit and adjusted for baseline use and total duration. Results: In our multivariable models after adjusting for significant covariates, we found that TNFi use was associated with less new bone formation in AS with the strongest association in patients who had 2.1–3.5 years of follow-up (OR=0.27; 95% CI 0.08–0.94; p=0.04) [Table 1 ]. Though not statistically significant, in patients who were followed up for 3.6 years or longer, the odds of progression for the TNFi user group was 41% (3.6–5.9 year group) and 14% (6+ year group) lower than in non-users (OR=0.59, OR=0.86). We found a significant interaction (p=0.01) between NSAID use and TNFi in relation to radiographic progression. Those patients exposed to both TNFi and with high NSAID use had an OR for progression of 0.31, 95% CI 0.13–0.75, compared to those not on high dose NSAIDs (OR=1.23, 95% CI 0.41–3.66). Conclusions: TNFi are associated with less new bone formation in AS, and this appears to be modified by the use of NSAIDs. Disclosure of Interest: L. Gensler Consultant for: AbbVie, Amgen, Janssen, Novartis, UCB, J. Reveille: None declared, M. Ward: None declared, M. Brown Grant/research support from: Janssen, Abbvie, UCB, Leo Pharma, Complete Genomics, Consultant for: Abbvie, UCB, Janssen, Pfizer, Speakers bureau: Abbvie, UCB, Pfizer, UCB, M. Rahbar: None declared, M. Lee: None declared, M. Weisman Grant/research support from: UCB, Human Genome Sciences, Sanofi, Eli Lilly and Co, Genentech, Inc., Santarus Inc., EMD Serono, ChemoCentryx, GSK, Immunomedics Inc., Consultant for: Boehringer Ingelheim/Proskauer, Ardea Biosciences, Epirus Biopharmaceuticals, Acerta Pharma